Safety distance control for multi-car lifts. (November 2016) - Gerstenmeyer, Stefan; Peters, Richard
The efficient use of lift shafts has becoming increasingly important because of the trend towards building taller buildings. In traditional lift systems only one lift car travels up and down a shaft. Systems with two independent cars in one shaft exist. If multiple cars are moving together in one or multiple vertical shafts certified safety systems ensure a minimum distance between cars at any time. The lift control system needs to control the distance between cars during normal and unexpected operation. This paper considers the stopping distance for a certified safety system and describes the theory and mathematics needed to determine controlled stopping positions and safety distances for lift control in a multi-car lift system. The minimum distance possible between two cars while levelling and standing at floors as well as the possible distance between cars while travelling during normal operation is calculated. Practical application : In lift systems with multiple cars travelling in one or multiple shafts, control strategies need to consider safety distance constraints. The lift control also needs to stop cars in unexpected situations with a controlled deceleration before the certified safety systems are forced to stop the cars in an uncontrolled manner to avoid collision. To monitor this critical distance and to ensure operation without unexpected deceleration the equations derived in this paper are necessary and can be applied to lift control systems.